UNISON DECISION ANALYSIS FRAMEWORK FOR WORKFORCE PLANNING FOR SEMICONDUCTOR FABS AND AN EMPIRICAL STUDY - Lin, Yun-Hsuan; Chien, Chen-Fu; Yu, Chih-Min (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
With the increase in the scale of semiconductor manufacturing, the number of knowledge-workers has also increased tremendously. The cost of automation and manpower is increasing annually, and engineers and technical operators are playing an increasingly crucial role in factories. The optimal workforce plan for manufacturing and the improvement of productivity have become key topics. In semiconductor manufacturing, numerous factors affect the workforce plan for manufacturing. The problem of determining the actual manpower demand, given the different preference structures of various decision makers, is difficult to solve. This study employed a UNISON decision analysis framework for constructing an workforce planning decision model for semiconductor manufacturing. We also held discussions with domain experts to identify key performance indices for human capital management. An empirical study was conducted in a semiconductor company, and the results showed that the proposed framework could assist the company in developing an operation workforce planning model and an associated management mechanism for improving the decision quality and decision rationality. Thus, the company could enhance human capital and productivity to maintain corporate competitiveness.